Hambatan dan Solusi dalam Implementasi Sistem Blok di SMK Negeri 4 Kota Serang - Rizky Sabili Salam; Ardhika Achmad Gustama; Wahyu Hidayat; Faisal Haris; Julian Muhammad Zaky; Andika Cahya Febriawan; Agus Gilang Hermawan; Gelen Veranda Deanda; Nur Alifah; Putri Andini Maulana; Elfriza Putri Indrayanti; Tiara Aprilia Kulsum; Atep Iman (Student Research Journal, 2025)
Vocational education, especially in Vocational High Schools (SMK), has an important role in preparing competent and skilled human resources (HR) to meet the needs of the world of work. In facing the challenges of evolving technology, the block system is applied as a learning innovation to align education with industry needs. This system allows students to focus on mastering productive competencies through structured learning, such as Field Work Practices (PKL) and productive subjects. This research uses a descriptive qualitative method with observation and interviews to evaluate the implementation of the block system at SMK Negeri 4 Serang City. The results showed that the block system has great potential in improving students' confidence and competence, but obstacles such as limited facilities, schedules, and teacher training are still the main challenges. Efforts to overcome these obstacles include cooperation between schools, parents and industry, as well as increasing teacher capacity through training. With planned implementation and optimal support from all parties, the block system can contribute significantly to producing graduates who are competent, disciplined and ready to compete in the job market.